Plasma levels of tumour necrosis factor- ain patients with chronic periodontitis and type 2 diabetes - S. Engebretson (Blackwell Science, 2007)
Objectives: Studies suggest that elevated circulating tumour necrosis factor-a (TNF-a) may contribute to insulin resistance in patients with type 2 diabetes. The source of plasma TNF has been thought to be adipocytes associated with obesity, but inflammation and infection result in TNF-a production as well. Methods: We studied 46 patients with type 2 diabetes and chronic periodontitis to determine the relationship between plasma TNF-a levels and clinical measures of periodontitis, gingival crevicular fluid (GCF) interleukin-1b (IL-1b), plasma endotoxin, serum glucose, and glycated haemoglobin (HbA1c). TNF-a levels were measured using a high sensitivity enzyme-linked immunosorbent assay. Results: TNF-a showed a significant positive correlation with attachment loss (r50.40, p50.009), plasma endotoxin (r50.33, p50.03), and GCF IL-1b (r50.33, p50.035), but not probing depth (r50.28, p50.07), bleeding on probing (r50.30, p50.053), plaque index (r50.22, p50.17), serum glucose, HbA1c (r50.10, p50.50), or body mass index (r50.077, p50.62). A dose– response relationship was observed between periodontitis severity and TNF-a ( p50.012). Conclusion: The finding that chronic periodontitis is associated with plasma TNF-a levels in subjects with type 2 diabetes supports the hypothesis that periodontal infection and inflammation may contribute to insulin resistance.